PENGARUH JENIS BAHAN PIPA PADA PEMANASAN BAHAN BAKAR DAN PENAMBAHAN ETANOL PADA PREMIUM TERHADAP EMISI GAS BUANG SUZUKI SHOGUN SP 125 TAHUN 2008 SEBAGAI BAHAN AJAR MATA KULIAH MOTOR BAKAR - Ahkyat, Farthur (Jurnal Nosel, 2016)
The results of research are as follows: 1) In the aluminum pipe heating the lowest level of (CO) was 0.149 (% vol) at the fuel blend of 70% premium and 30% ethanol, and the fuel temperature following heating was 62.1 °C meaning that the level of (CO) declines below the standard condition without the fuel heating treatment. 2) In the stainless steel pipe heating, the lowest level of (CO) was 0.158 (% vol) at the fuel blend of 70% premium and 30% ethanol and the fuel temperature following the heating was 62.1 °C, indicating that the level of (CO) declines below the standard condition without the fuel heating treatment. 3) In the copper pipe heating, the lowest level of (CO) was 0.159 (% vol) at the fuel blend of 70% premium and 30% ethanol with the fuel temperature following the heating was 61.7 °C, meaning that the level of (CO) declines below the standard condition without the fuel heating treatment. 4) In the aluminum pipe heating, the lowest level of (HC) was 215 (ppm vol) at the fuel blend of 100% premium, and the fuel temperature following the heating was 54.1 °C meaning that level of (HC) is above the standard condition without the fuel heating treatment. 5) In a stainless steel pipe heating, the lowest level of (HC) was 136 (ppm vol) at the fuel blend of 95% premium and 5% ethanol, and the fuel temperature following the heating was 54.1 °C, meaning that the level of (HC) declines below the standard condition without the fuel heating treatment. 6) In the copper pipe heating, the lowest level of (HC) was 100 (ppm vol) at fuel blend of 95% premium and 5% ethanol, and the fuel temperature following the heating was 61.2 °C, meaning that the level of (HC) declines below the standard condition without fuel heating treatment.